Norwid’s Visual Metaphors on the Example of “Fortepian Szopena” (“Chopin’s Pianoforte”) - Niewczas, Łukasz (Colloquia Litteraria, 2018)
The article deals with the analysis of the visual metaphor present in Norwid’s writings. The author’s microanalyses point to a certain type of ‘semiotic image’ prevalent in Norwid’s literary output.